Job satisfaction among Indian pharmacists: an exploration of affecting variables and suggestions for improvement in pharmacist role - Ahmad, Akram; Khan, Muhammad Umair; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim; Nagappa, Anantha Naik; Patel, Isha; Balkrishnan, Rajesh (Association of Pharmaceutical Teachers of India (APTI), 2015)
Objectives: The purpose of this study was to determine the level of job satisfaction among Indian pharmacists, and factors associated with job satisfaction. The study also explored the suggestions of pharmacist to improve the profession of pharmacy in India. Methods: A cross sectional web-based study was conducted on working pharmacists in India, using a validated questionnaire for a period of 2 months. The participants were contacted via email and social websites and data was collected by using web-based survey. The data were coded and entered to statistical package for social sciences (SPSS) version 20. The responses to the questionnaire were analyzed by performing descriptive and inferential statistics. Results: The satisfaction rate of pharmacists was 17.5%. Similar numbers of pharmacist were satisfied with promotional opportunities at their workplace. 68.7% participants believed the reason for dissatisfaction was irresponsible government policies which hamper pharmacists from seeking jobs compared with other professionals. Majority of pharmacists agreed with the suggestion of determining payscale on the basis of both qualification and experience (85.1%) followed by 84.8% who agreed that pharmacy degree should be deemed essential to acquire registration. Age, qualification and practice setting were significantly associated with differences in mean satisfaction score (p<0.05). Conclusion: In this study, pharmacists were not satisfied with their jobs. A nation-wide study is warranted to further establish the satisfaction of pharmacists with their jobs. A further need to look at the intrinsic and extrinsic factors associated with pharmacist satisfaction can aid the development of suitable interventions to improve the same.